Chapter The economic revolution in book design that went unnoticed. The case of the Southern Netherlands, 1473-c. 1550 - Proot, Goran (Datini Studies in Economic History, 2023)
This contribution discusses the evolution of paper thickness of books produced in the Southern Netherlands in the period 1473 until the middle of the sixteenth century. Changing paper thickness is one of the key elements which in all likelihood helped coping with the problem of the rapidly increasing demand for paper by the press. After a description of relevant aspects of the production of hand laid paper and of the resulting morphology of sheets, a methodology is proposed to deal with the problem of establishing paper thickness in bound volumes and further problems dealing with the compression effect and of binding and rebinding are discussed.